Electrochemical Detection of Nitrite Using a Fe₃O₄/Nafion-Modified Gold Wire Electrode - Ruzain Rafie Sukma Putra; Harmami; Kartika A Madurani; Heru Suryanto; Daimon Syukri; Masato Tominaga; Fredy Kurniawan (Proceeding of International Joint Conference on UNESA, 2025)
This study presents the development and evaluation of an electrochemical sensor for nitrite detection based on magnetite nanoparticles (Fe₃O₄ NPs) and a Nafion-modified gold wire electrode. Fe₃O₄ NPs were synthesized through an electrolysis route and subsequently characterized using X-ray diffraction (XRD) and field emission scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (FE-SEM/EDX). The XRD diffraction pattern is similar to the standard JCPDS card number 19-0629, confirming the structure of Fe₃O₄ NPs. Morphology analysis using FE-SEM revealed Fe₃O₄ NPs with an average size measured to be 123.4 nm. Cyclic voltammetry (CV) measurements demonstrated a high oxidation peak for nitrite detection using the proposed electrode at neutral pH (pH 7). CV analysis towards K3[Fe(CN)6] shows that the proposed electrode gave the highest current peak. The specific surface area of the proposed electrode was found to be 0.149 cm2. Quantitative analysis using CV showed a limit of detection (LOD) of 4.4 ppm. Using the amperometry techniques, the LOD produced was as low as 0.00105 ppm. These findings highlight the potential of the Fe₃O₄ and Nafion-modified gold electrode for sensitive nitrite analysis.